2009
DOI: 10.1016/j.jtbi.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling chemotherapy resistance in palliation and failed cure

Abstract: a b s t r a c tThe goal of palliative cancer chemotherapy treatment is to prolong survival and improve quality of life when tumour eradication is not feasible. Chemotherapy protocol design is considered in this context using a simple, robust, model of advanced tumour growth with Gompertzian dynamics, taking into account the effects of drug resistance. It is predicted that reduced chemotherapy protocols can readily lead to improved survival times due to the effects of competition between resistant and sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(98 citation statements)
references
References 33 publications
(50 reference statements)
5
93
0
Order By: Relevance
“…The authors found that in general, cytotoxic drugs alone are insufficient to eradicate the tumor, since there are two main barriers to achieving a complete remission of the tumor: evolving populations tend to produce resistant clones which are able to drive the system back to an equilibrium abundance, and drug-induced alterations of the tumor microenvironment change the selection pressure and select for tumor cells with larger evolvability. In 2009, Monro and Gaffney modeled the dynamics of chemotherapy resistance in a model of palliative treatment, when tumor eradication is not feasible [95]. In such cases, the goal of treatment is to prolong survival and improve the quality of life.…”
Section: Previous Workmentioning
confidence: 99%
“…The authors found that in general, cytotoxic drugs alone are insufficient to eradicate the tumor, since there are two main barriers to achieving a complete remission of the tumor: evolving populations tend to produce resistant clones which are able to drive the system back to an equilibrium abundance, and drug-induced alterations of the tumor microenvironment change the selection pressure and select for tumor cells with larger evolvability. In 2009, Monro and Gaffney modeled the dynamics of chemotherapy resistance in a model of palliative treatment, when tumor eradication is not feasible [95]. In such cases, the goal of treatment is to prolong survival and improve the quality of life.…”
Section: Previous Workmentioning
confidence: 99%
“…In those cases, the goal of chemotherapy is to extend survival and improve the quality of life. On this subject, Monro and Gaffney (Monro and Gaffney, 2009) asked whether an intermediate level of chemotherapy would restrict tumor growth and increase the time of survival in a palliative setting. Their populations model based on ODEs predicted that reduced chemotherapy protocols could lead to longer survival times due to competition between resistant and sensitive tumor cells (Fig.…”
Section: Mathematical Modeling Of Mdrmentioning
confidence: 99%
“…8-week) patient-level changes in tumour burden over time and in response to treatment. TUK models have also been used to inform Phase III clinical trial designs or to inform clinical dosing regimens, as originally considered by Goldie and Coldman [27,28]. Multivariate survival models may then be developed that link baseline patient characteristics and model-derived metrics, such as tumour growth rates, to longer-term overall survival (OS) [2,26].…”
Section: Application Of Models To Predict Tumour Progression and Respmentioning
confidence: 99%
“…3d). TUK models have also been used to inform Phase III clinical trial designs or to inform clinical dosing regimens, as originally considered by Goldie and Coldman [27,28]. For example, an in silico model [29] was used to demonstrate that tumours that become small in response to therapy may become resistant, so would require dense, intensive therapy to prevent remission.…”
Section: Application Of Models To Predict Tumour Progression and Respmentioning
confidence: 99%